If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -8y + -6 = 0 Reorder the terms: -6 + 2x + -8y = 0 Solving -6 + 2x + -8y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 2x + 6 + -8y = 0 + 6 Reorder the terms: -6 + 6 + 2x + -8y = 0 + 6 Combine like terms: -6 + 6 = 0 0 + 2x + -8y = 0 + 6 2x + -8y = 0 + 6 Combine like terms: 0 + 6 = 6 2x + -8y = 6 Add '8y' to each side of the equation. 2x + -8y + 8y = 6 + 8y Combine like terms: -8y + 8y = 0 2x + 0 = 6 + 8y 2x = 6 + 8y Divide each side by '2'. x = 3 + 4y Simplifying x = 3 + 4y
| 4d+18+9d= | | (2x-3)-(4x-5)=6y | | 7(x-4.5)=2.8 | | -4+r+20= | | t*2-1= | | n(3n+2)=1 | | x^8-15x^7-16x^6= | | 27a^3+8b^3=0 | | 17+11r+15m-2r-4m-16= | | 4x-1+x+15=180 | | 6x-7.80=97.20 | | 4x=16+3x | | 7+11x-4=7x+59-4x | | -4x-7=-5x-1 | | -12y-10=-by+14 | | 15x+8y+1z=90 | | X-2+5x= | | (3x)(3x)-2x-1=0 | | 4+0+n= | | 8x-9+5=7x+3 | | 6x-13-2x=6x-8 | | 6[1-n]=-6n+1 | | 82=7(x+6)-2 | | -x^2-7x+196=0 | | 5(6-x)=1.3(4-x) | | 8x?9+5x=7x+3 | | 4x^2-2y=20 | | 4[x-4]=2x | | x-15*-4=14 | | 8-4x+8x+3y= | | -7(x-9)-3=60 | | 14.19+0.08=14.94+0.15 |